Seed Coating with Arbuscular Mycorrhizal Fungi for Improved Field Production of Chickpea - Rocha, Inês (2020)
Although arbuscular mycorrhizal (AM) fungi are known to promote growth and yield of agricultural crops, inoculation methods for effective scaling up from greenhouse to the field are still underexplored. The application of single or mixed beneficial AM fungal isolates is hindered by the lack of experimental reproducibility of findings at different scales and the cost-effectivity of inoculation methods. Seed coating has been considered a feasible delivery system of AM fungal inocula for agricultural crops. In this study, the impact of single and multiple AM fungal isolates applied via seed coating on chickpea productivity was evaluated under greenhouse and field conditions. Overall, plants inoculated with multiple AM fungal isolates had better performance than those inoculated with single AM isolate under greenhouse and field conditions. While plants in greenhouse displayed higher shoot dry weight (14%) and seed individual weight (21%), in field, inoculation with multiple AM isolates increased pod (160%), and seed (148%) numbers, and grain yield (140%). Under field conditions, mycorrhizal root colonization was significantly higher in chickpea plants inoculated with multiple AM fungal isolates compared to other treatments. These findings highlight the potential of field-inoculation with multiple AM fungal isolates via seed coating as a sustainable agricultural practice for chickpea production.